Answer:
Step-by-step explanation:
A = length x width
l = x + 5
w = x
A = x(x + 5)
10 + 2³ ∙ 4 - 1
10 + 2³ ∙ (4 - 1)
(10 + 2³) ∙ 4 - 1
10 + (2³ ∙ 4) - 1
Hello there!
10+2^3*4-1
10+8*4-1
10+32-1
10+31
41
10+2^3*(4-1)
10+8*(3)
10+24
34
(10+8)*4-1
18*4-1
72-1
71
10+(2^3*4)-1
10+(8*4)-1
10+32-1
10+31
41
Hope this helps you!
Additional comment
If you found my answer helpful, please mark Brainliest!
if it's wrong, please don't report. Just rate 4 stars. Thanks! :)
C=2πr solve for r
Part B: Explain in words how to graph the solution to the inequality on a number line. (4 points)
Part C: Find two values that would make the inequality true. Explain how you know the values are solutions to the inequality. (4 points)
Answer: Sure, I can help you with that!
Part A: To solve the inequality −6(x − 3) > 42, we first need to distribute the -6 to the expression inside the parentheses:
-6(x - 3) > 42 -6x + 18 > 42
Next, we’ll subtract 18 from both sides:
-6x > 24
Finally, we’ll divide both sides by -6. Since we’re dividing by a negative number, we need to flip the inequality sign:
x < -4
Therefore, the solution to the inequality is x < -4.
Part B: To graph the solution to this inequality on a number line, we’ll start by drawing an open circle at -4 (since x is not equal to -4). Then, we’ll draw an arrow pointing to the left of -4 to indicate that all values less than -4 are solutions to the inequality.
Part C: To find two values that would make the inequality true, we can choose any two values less than -4 and substitute them into the original inequality. For example, if we choose x = -5, then:
-6(-5 - 3) > 42 -6(-8) > 42 48 > 42
Since 48 is greater than 42, this confirms that x = -5 is a solution to the inequality. Similarly, if we choose x = -10, then:
-6(-10 - 3) > 42 -6(-13) > 42 78 > 42
Since 78 is also greater than 42, this confirms that x = -10 is also a solution to the inequality.
I hope this helps!
Runfast= $35 per month
BA&D= $33 per month
widgets produced. The selling price, S, of each widget in selling price be if 15 widgets are produced?
dollars is a function of the production cost per unit
C(x) = -0.1x2 + 100
O C(S(x)) = -0.196x2 + 100, $108.64
S(C) = 1.40
O C(S(x) = -0.196x2 + 100; $55.90
O S(C(x)) = -0.14x2 + 140; $144.41
O S(C(x)) = -0.14x2 + 140, $108.50
Answer:
S(C(x)) = –0.14x2 + 140; $108.50
Step-by-step explanation:
did the assignment
Answer:
S(C(x)) = -0.14x2 + 140, $108.50